Tradução, adaptação transcultural e validação do instrumento psoriatic arthritis screening and evaluation (pase) para a língua portuguesa brasileira - Costa, Carolina Zorzanelli (2015)
The psoriatic arthritis (PsA) is a rheumatologic disease that affects the musculoskeletal system (arthritis) and the skin (psoriasis). It can have a severe impact on the quality of life of those who suffer from this illness; then, the early detection of the PsA is an extremely important purpose. In 70% of the cases, this disease starts with skin problems, so that the patient monitors it exclusively at a dermatologist s office. However, there are no valid and reliable tools in Portuguese to assist dermatologists in the early diagnosis of PsA. This study aimed to translate, culturally adapt and validate the PASE (Psoriatic Arthritis Screening and Evaluation) in Brazilian Portuguese. This tool is a self-administered questionnaire developed in English to screen arthritis in patients with diagnosis of psoriasis. The process of translation and adaptation followed international protocols on this matter, whose steps included translation, reconciliation, back translation, cognitive interview, independent review and a revision performed by the linguistic team of the author of this questionnaire. After these steps, the translation was pretested on 50 individuals. The final version was applied to 465 patients with psoriasis (158 with psoriatic arthritis and 307 without it) in four Brazilian university hospitals, and the data collected was submitted to quality tests (missing data, floor and ceiling effects). The psychometric properties of the tool were verified by known-groups validity, item-discriminant validity, item-internal consistency, Cronbach\'s alpha, intraclass correlation coefficient and confirmatory factor analysis. In the cognitive interview, some changes were performed in the translation due to cultural adaptation. There was no missing data. The floor effect was present in all the items of the two subscales and the ceiling effect was observed in four items of the first subscale and in two items of the second subscale. The reliability verified through the item-internal consistency (100% success), the Cronbach\'s alpha coefficients (0.92), and the intraclass correlation (0.97) were considered adequate. The known-groups and the item-discriminant validity achieved appropriate results. The confirmatory factor analysis provided a proper fit according to the variables observed (X2 = 247.1, p <0.001; df = 79; X2/df = 3.12; GFI = 0.93, AGFI = 0.90, CFI = 0.95; SRMR = 0.04; RMSEA = 0.07). The results showed that the PASE-P (translated version of the PASE) is a valid and reliable tool to be used in Brazil.